The Effect of Exercise on the Older Adult’s Blood Pressure Suffering Hypertension: Systematic Review and Meta-Analysis on Clinical Trial Studies - Mohsen Kazeminia; Alireza Daneshkhah; Rostam Jalali; Aliakbar Vaisi-Raygani; Nader Salari; Masoud Mohammadi (International Journal of Hypertension)
Background. Senescence refers to spontaneous and progressive irreversible degenerative changes in which both the physical and psychological power diminish significantly. Hypertension is the most common cardiovascular disease in the elderly. Several studies have been conducted regarding the effect of exercise on reducing the blood pressure of the elderly, which have found contradictory results. One of the uses of meta-analysis study is responding to these assumptions and resolving the discrepancies. Accordingly, the aim of the present study is to determine the impact of exercise on the blood pressure of older adults. Method. In this research, in order to find electronic published papers from 1992 to 2019, the papers published in both domestic and foreign databases including SID, MagIran, IranMedex, IranDox, Gogole Scholar, Cohrane, Embase, Science Direct, Scopus, PubMed, and Web of Science (ISI) were used. Heterogeneity index between the studies was determined based on Cochran test Q(c) and I2. Considering existence of heterogeneity, random effects model was employed to estimate the standardized subtraction of the mean exercise test score for reduction of blood pressure in the older adults across the intervention group before and after the test. Results. In this meta-analysis and systematic review, eventually 69 papers met the inclusion criteria. The total number of participants was 2272 in the pre- and postintervention groups when examining the systolic changes and 2252 subjects in the pre- and postintervention groups when inspecting the diastolic changes. The standardized mean difference in examining the systolic changes before the intervention was 137.1 ± 8.09 and 132.98 ± 0.96 after the intervention; when exploring the diastolic changes, the pre- and postintervention values were 80.3 ± 0.85 and 76.0 ± 6.56, respectively, where these differences were statistically significant (P<0.01). Conclusion. The results of this study indicated that exercise leads to significant reduction in both systolic and diastolic blood pressure. Accordingly, regular exercise can be part of the treatment plan for hypertensive elderly.